(untitled) (Revista de Estudos Sociais, 2021)
This article investigates the impact of trade openness and renewable energy on the consumption of fossil fuels for a panel of fourteen LAC countries over the period from 1990 to 2014. To this end, a PARDL model in unrestricted error-correction form is estimated, and robustness checks are performed by estimating a PNARDL model. The results of the PARDL model point indicate that the impact of economic growth and elasticity of trade openness are statistically significant at the 1% level and contribute to increased consumption of fossil fuels in the LAC countries. However, the impact and elasticity of consumption of renewable energy are statistically significant at 1% and 5% levels and thus contribute to decreasing consumption of fossil fuels. Nevertheless, the asymmetry of the impact of consumption of renewable energy and its elasticity decrease the consumption of fossil fuels. Therefore, the positive impact of trade openness on the consumption of fossil fuels suggests that the process of globalisation by trade liberalisation in the LAC countries is not sufficient to bring more investment that encourages R&D in energy efficiency technologies, and equipment that reduces the consumption of energy from non-renewable energy sources by households and firms.